Transcatheter Device Closure of a Congenital Aortic–Left Atrial Tunnel. (22nd April 2013) - Sun, Heather Y.; Buccola, Katie Jo; Punn, Rajesh; Silverman, Norman H.; Peng, Lynn F.; Perry, Stanton B.; Balasubramanian, Sowmya
Abstract Rare cases of aortic–left atrial tunnel exist in the literature. This case report highlights the echocardiographic characterization of this vascular anomaly and provides the first description of an aortic–left atrial tunnel closed by interventional cardiac catheterization in a pediatric patient.